Work-related musculoskeletal Disorders: Prevalence in restaurant workers (Research, Society and Development, 2021)
The aim of this study was to analyze the prevalence of Work-Related Musculoskeletal Disorders (WMSD) in university restaurant workers. This is a cross-sectional and descriptive study with workers from four university restaurants in Belo Horizonte/MG. WMSD assessment in the last twelve months was investigated using the Nordic Musculoskeletal Symptoms Questionnaire (QNSO), composed of closed questions and organized by thematic sets that included demographic, socio-familial, health self-assessment, anthropometric variables, occupational characteristics and musculoskeletal symptoms. self-reported. Data were tabulated and analyzed by SPSS (p